2017
DOI: 10.1177/0959354317718970
|View full text |Cite
|
Sign up to set email alerts
|

Positive psychology’s promise of happiness: A new form of human capital in contemporary neoliberal governmentality

Abstract: The article seeks to contribute to governmentality studies by looking anew at the subjectivities posited by neoliberalism and especially by positive psychology. Focusing in particular on Sam Binkley’s critical work on this psychological sub-discipline, we offer a political analysis of the new ways of becoming a subject it proposes. For Binkley, positive psychology operates as a subjectivising vector by promoting a specific kind of work on oneself. His approach, we suggest, rests on a conception that relies on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 35 publications
1
28
0
2
Order By: Relevance
“…Hegemonic perspectives of psychological science typically impose a neoliberal individualist construction of happiness as high arousal positive affect (Tsai, ). According to this standard, it is not sufficient to achieve contentment or absence of negative feelings; in addition, psychologists tend to prescribe the more active or energetic form of happiness that fulfills requirements of neoliberal affect management: namely, to motivate entrepreneurial risk and to counter anxiety associated with responsibilization of failure (De La Fabian & Stecher, ).…”
Section: Psychological Science As a Site For Reproduction Of Neolibermentioning
confidence: 99%
“…Hegemonic perspectives of psychological science typically impose a neoliberal individualist construction of happiness as high arousal positive affect (Tsai, ). According to this standard, it is not sufficient to achieve contentment or absence of negative feelings; in addition, psychologists tend to prescribe the more active or energetic form of happiness that fulfills requirements of neoliberal affect management: namely, to motivate entrepreneurial risk and to counter anxiety associated with responsibilization of failure (De La Fabian & Stecher, ).…”
Section: Psychological Science As a Site For Reproduction Of Neolibermentioning
confidence: 99%
“…Work-based resilience initiatives, discussed above, often incorporate related ‘positive’ coping strategies (Bardoel et al, 2014; Pykett, Jones, & Whitehead, 2016). Indeed, some critics argue that happiness at work, as promoted through positive psychology, has become a valuable form of cultural capital that equips those who are already successful to become even more so (De La Fabián & Stetcher, 2017). So the workers in our study might be said to possess both cultural capital and work environments that best set them up for workplace success and happiness.…”
Section: Analysis and Findings: Four Themes Relevant To The Experiencmentioning
confidence: 99%
“…It could be argued that positive psychology itself betrays an individualistic bias that reflects neoliberalism and governmentality, and indeed such criticisms have been leveled (e.g., Cabanas, 2018;De La Fabián & Stecher, 2017). However, it has also been suggested that the critical perspective may represent an over-intellectualization of economic rationalization (Fleming, 2014).…”
mentioning
confidence: 99%